THE IMPLEMENTATION OF INDONESIAN EMPLOYMENT LAW IN PROTECTING THE WELFARE RIGHTS OF INDONESIAN MIGRANT WORKERS ACCORDING TO ISLAMIC LAW - Imron, Ali; Abd. Qadir Gassing; Hasyim Aidid; Marilang (Jurnal Diskursus Islam, 2022)
This paper elaborates on implementing Indonesian employment law in protecting the welfare rights of Indonesian Migrant Workers according to Islamic law. This type of research was field research of descriptive qualitative with a case study design. The primary data sources of this study were the Ministry of Employment and The National Agency of Placement and Protection of Indonesian Migrant Workers. The data collection techniques include observation, purposive interview, snowball sampling, documentation, and literature review. The approaches used were juridical, sociological, and normative theological approaches. The data obtained were then analyzed by data reduction techniques, presentation, concluding, and data verification. The study results indicate the implementation of Indonesia’s employment law through the instruments of Constitution Number 13 of 2003 about Employment and Constitution Number 39 of 2004 concerning the Placement and Protection of Indonesian Migrant Workers Abroad (PPIMWA). The revision of Constitution Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers (PIMW) has empowered and employed Indonesian migrant workers optimally and humanely. The theory of Maqasid al-Syar’i‘ah takes the employment into the category of the essential five human elements (al-Daruriyyat al-Khamsu). It refers to religion, soul, lineage, property, and mind at the primary level (al-D{aruriyyat), then the legal protection of Indonesian migrant worker who is komprador in maintaining and preserving human rights must also be embodied.